Wonderstruck - Selznick, Brian (New York : Scholastic, 2011)
Having lost his mother and his hearing, twelve-year-old Ben leaves his Minnesota home in 1977 to seek his father in New York City, and meets Rose, who is also longing for something missing from her life. Ben's story is told in words; Rose's in pictures.
Includes bibliographical references (p. 635-637).
830
Keywords: American Museum of Natural History -- Juvenile fiction; Families -- Juvenile fiction; Diorama -- Juvenile fiction; Deaf -- Juvenile fiction; People with disabilities -- Juvenile fiction; Museums -- Juvenile fiction; Runaways -- Juvenile fiction; Deafness -- Juvenile fiction; Orphans -- Juvenile fiction; New York (N.Y.) -- History -- 20th century -- Juvenile fiction